Effect of Corporate Governance, Firm Characteristic, Disclosure of Corporate Social Responsibility (CSR) on Firm Value - Rahimah Bawai; Hermala Kusumadewi (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: This study aims to determine the effect of corporate governance, firm characteristics, disclosure of corporate social responsibility (CSR) on firm value. It analyzes the firms which became the participants of the 2014 Sustainability Report Award. Corporate governance is proxied by the proportion of independent commissioners, while firm characteristic is proxied through the age of the firm. Meanwhile, the disclosure of corporate social responsibility (CSR) in the sustainability report is stated in the Corporate Social Responsibility Index (CSRI). The firm value was calculated using the Tobins’Q formula. The hypothesis was tested using linear regression. The test results show corporate governance and firm characteristics have a positive effect on firm value. Meanwhile, corporate social responsibility (CSR) disclosure has a positive but insignificant effect on the dependent variable. If all independent variables are tested simultaneously, all three variables have a positive effect. However, disclosure of corporate social responsibility (CSR) has no significant effect.Keywords: corporate governance, firm characteristics, corporate social responsibility (CSR), firm value, sustainability report Pengaruh Corporate Governance, Karakteristik Perusahaan, Pengungkapan Corporate Social Responsibility (CSR) terhadap Nilai PerusahaanAbstrak: Penelitian ini untuk mengetahui pengaruh corporate governance, karakteristik perusahaan, pengungkapan corporate social responsibility (CSR) terhadap nilai perusahaan. Periode penelitian tahun 2014-2018 yang merupakan perusahaan peserta Sustainability Report Award 2014. Corporate governance diproksi dengan proporsi dewan komisaris independen. Kemudian karakteristik perusahaan diproksi melalui umur perusahaan yang dihitung dari tahun berdiri perusahaan dikurangi dengan tahun penelitian. Sedangkan pengungkapan corporate social responsibility (CSR) pada laporan sustainability report dinyatakan dalam Corporate Social Responsibility Index (CSRI) yang disyaratkan oleh Global Reporting Initiative (GRI). Variabel dependen nilai perusahaan dihitung menggunakan rumus tobins’Q. Pengambilan sampel menggunakan metode purposive sampling dengan jumlah sampel sebanyak 19 perusahaan. Pengujian hipotesis dengan regresi linear. Hasil pengujian menunjukkan corporate governance dan karakteristik perusahaan berpengaruh positif terhadap nilai perusahaan. Sedangkan pengungkapan corporate social responsibility (CSR) berpengaruh positif namun tidak signifikan. Jika seluruh variabel independen diuji secara bersamaan, ketiga variabel mempunyai pengaruh positif. Namun pengungkapan corporate social responsibility (CSR) tidak memiliki pengaruh yang siginifikan.Kata kunci: corporate governance, karakteristik perusahaan, corporate social responsibility (CSR), nilai perusahaan, sustainability report.